I spy school days : a book of picture riddles - Wick, Walter; Marzollo, Jean. (New York : Scholastic, 1995)
Rhyming text presents clues whose solutions can be found in the accompanying pictures.
"Cartwheel books."
3.0
K-3.
K-3
Keywords: Picture puzzles -- Juvenile literature; Picture puzzles; Picture puzzles; Picture books for children